Urban Resilience under Global Pressure: A Political Economy Analysis of the US–China Trade War and Its Impact on MSMEs in Indonesia - Alia, Mandra Nur; Pratamasari, Annisa (Universitas Wijaya Kusuma Surabaya, 2026)
This article examines how the US-China trade war reshapes the resilience of Micro, Small, and Medium Enterprises (MSMEs) in Indonesian urban economies. While existing studies primarily focus on macroeconomic consequences of global trade rivalry, this study situates MSMEs as socially embedded urban actors operating within spatially uneven market structures, informal economic networks, and localized consumption systems. Using a qualitative political economy approach based on literature review, policy analysis, and illustrative urban evidence from Surabaya and Jakarta, the article analyzes how global supply-chain disruptions, import competition, and financial tightening affect MSME sustainability at the city level. The findings demonstrate that MSMEs function not only as economic units but also as neighborhood-based infrastructures of social resilience that absorb labor displacement, stabilize household income circulation, and maintain local economic continuity under conditions of global uncertainty. However, adaptive capacity varies across urban spaces depending on infrastructure access, institutional support, and market connectivity. The study argues that MSME resilience should be understood as a spatially embedded relational process shaped by interactions between global political economy restructuring and localized social adaptation practices